KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI BERMAIN PLASTISIN DI TK KUMARA SARI IV SULANGAI DESA SULANGAI KECAMATAN PETANG KABUPATEN BADUNG - Raka Wirati I Gusti Ayu Putu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Fine motor skills are important abilities for children to have because they are related to the coordination of the child's fingers. Fine motor development is the development of a movement that includes small muscles with eye-hand coordination. The problems that will be discussed include (1) How is the learning process carried out in children's fine motor skills through playing plasticine at Kumara Sari IV Kindergarten Sulangai? (2) What are the obstacles experienced by teachers in developing children's fine motor skills through playing with plasticine at Kumara Sari IV Kindergarten, Sulangai? (3) What is the impact of playing with plasticine on the fine motor skills of children at Kumara Sari IV Kindergarten, Sulangai? The purpose of this study is to describe the fine motor skills of children through playing with plasticine at TK Kumara Sari IV Sulangai. The theory used is the theory of constructivism from Jean Piaget, the theory of Montessori learning and the learning theory of Frederich Wilhelm Froebel. This type of qualitative research. The research subjects were class B teachers, group B students. The method of collecting data was through participant observation, structured interviews, document studies and literature studies. Data analysis is data reduction, data classification and data presentation. The results of the study say (1) the learning process is carried out through three stages, namely the planning stage, the implementation stage and the evaluation stage. (2) The obstacles experienced by teachers are the lack of teaching staff, plasticine media requires quite a lot of costs and different levels of intelligence of children. (3) Positive impacts include well-trained fingers, children can recognize shapes, train children's creativity, children can recognize numbers and letters, children can recognize colors, keep children away from gadgets. The negative impact is that the child becomes addicted to plasticine and is dangerous if swallowed by the child.